Instantaneous wave-free ratio for the assessment of nonculprit lesions in patients with acute coronary syndrome. (14th October 2021) - Gonzalez-Manzanares, R; Hidalgo, F J; Ojeda, S; Piserra, A; Perea-Armijo, J; Rodriguez-Nieto, J; Flores, G; Suarez De Lezo, J; Benito-Gonzalez, T; Gutierrez-Barrios, A; De La Torre, J M; Mazuelos, F; et al.
Abstract: Background: A physiological assessment with the fractional flow reserve (FFR) or instantaneous wave-free ratio (iFR) is strongly recommended by the European Guidelines of Revascularization to guide percutaneous coronary intervention (PCI) decision making in intermediate coronary stenosis. However, data supporting its use in the pro-inflammatory setting of ACS is weak. Purpose: To analyze the usefulness of a physiological coronary evaluation with iFR of nonculprit lesions in patients with ACS. Methods: Retrospective multicenter study including patients with ACS and underwent successful revascularization of the culprit vessel and had other nonculpritlesions physiologically evaluated with the iFR between January 2017 and December 2019. The primary endpoint was a composite of cardiac death, nonfatal myocardial infarction, stent thrombosis and new revascularization (MACEs). Results: A total of 356 patients with 472 nonculprit lesions were included. The mean age was 66±11 years. The clinical presentation was non-ST-segment elevation myocardial infarction (NSTEMI) in 235 patients and ST-segment elevation myocardial infarction (STEMI) in 121 patients. After a mean follow-up period of 22±10 months, the primary endpoint occurred in 32 patients (9%). There were no differences in outcomes regarding iFR induced treatment strategy (patients with all lesions revascularized vs. patients with at least one lesion deferred for revascularization, 10.5 vs 8.4%, p=0.476). Conclusion: The use of the iFR to guide percutaneous coronary intervention decision making in nonculprit lesions seems to be safe, with an acceptable percentage of MACEs at the mid-term follow-up. FUNDunding Acknowledgement: Type of funding sources: None.